LIDDLE'S SYNDROME - Aziz, Danish Abdul; Memon, Fozia; Rahman, Arshalooz; Ali, Madiha (Journal of Ayub Medical College Abbottabad, 2016)
Hypertension in paediatric age group is commonly secondary to a known cause. It is crucial to identify the cause of hypertension and treat it before development of any associated complications to prevent morbidity and mortality. Paediatric Hypertension is one of the important clinical finding in a child with certain clinical syndrome. We are presenting a case of a 10 month old child presenting with hypertension and hypokalaemia, after excluding all identifiable causes and her positive response to therapy, that is amiloride, along with supportive biochemical data she was diagnosed as a case of monogenic type of hypertension known as Liddle's syndrome. Keywords: Paediatric Hypertension; Liddle's Syndrome; Epithelial sodium channel (ENaC); Hypokalemia; Potassium sparing diuretics; Plasma Renin Activity (PRA)